PTFE coated sodium ion battery active material and preparation method thereof

Through the active material of sodium ion battery coated with PTFE, the problems of low electron conductivity and high charge transfer resistance during the cycle of sodium ion batteries are solved, and the SEI interface layer with high ion transfer rate and mechanical strength is realized, which improves sodium ions The cycling stability and electrochemical properties of the battery promote their commercial applications.

CN119230786APending Publication Date: 2024-12-31GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411451812.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing sodium ion batteries have problems such as low electronic conductivity, high charge transfer resistance, poor capacity performance stability and unstable cycle during the cycle, which affect their commercial application.

Method used

Using PTFE-coated sodium ion battery active material, a SEI interface layer with high ion transfer rate and high mechanical strength is prepared by mixing polytetrafluoroethylene with hard carbon or sodium vanadium phosphate in a specific proportion, for sodium ion battery Positive and negative electrode materials.

Benefits of technology

It significantly improves the cycle stability and electrochemical performance of sodium ion batteries, reduces the preparation cost, and promotes the commercial application of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230786A_ABST
    Figure CN119230786A_ABST
Patent Text Reader

Abstract

The invention is suitable for the field of battery materials, and provides a PTFE coated sodium ion battery active material, which comprises polytetrafluoroethylene and an active matter, and the mass ratio of the polytetrafluoroethylene to the active matter is (0.02-0.09): 1 or (0.2-0.3): 1. The embodiment of the invention also provides a preparation method of the PTFE coated sodium ion battery active material. According to the invention, PTFE is adopted to modify the active matter of the sodium ion battery, and by controlling the dosage ratio of PTFE to the active matter, the PTFE coated sodium ion battery active material has an SEI interface layer with high ion transmission rate and high mechanical strength. The preparation method disclosed by the invention is simple and rapid, is relatively low in preparation cost, and has important significance for realizing commercialization of the sodium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a PTFE-coated sodium ion battery active material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have advantages such as high specific energy, long cycle life and low self-discharge rate, and are widely used in portable electronic devices and electric vehicles. Although lithium-ion batteries are currently the main commercial batteries on the market, they also have many obvious disadvantages during use: (1) Safety and thermal management: Lithium-ion batteries have safety hazards under conditions such as overcharging, over-discharging, and high temperature, which can easily cause battery failure or even explosion and fire. (2) Cost and material sustainability: The cost of lithium-ion batteries is still relatively high, mainly due to the scarcity of lithium metal and the large-scale use of lithium and the complexity of the manufacturing process of other materials. (3) High internal impedance. Since the electrolyte of lithium batteries is an organic solvent, its conductivity is much lower than that of nickel-cadmium batteries and nickel metal hydride batteries. Therefore, the internal impedance of lithium batteries is higher than that of nickel-hydrogen batteries and nickel-cadmium batteries.

[0003] The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Since sodium resources are abundant and cheap, sodium-ion batteries have the advantage of low cost. In addition, sodium-ion batteries are also characterized by high safety and high energy density, so sodium-ion batteries have gradually become the object of extensive research. However, the reaction kinetics and cycle life of sodium-ion batteries are still lower than those of lithium-ion batteries; sodium-ion batteries are prone to form unstable SEI during the cycle process, resulting in waste of electrolyte and consumption of sodium ions. Therefore, designing and constructing an SEI interface layer with high ion transfer rate and high mechanical strength is of great significance for the commercialization of sodium-ion batteries. Summary of the invention

[0004] In view of this, the present invention provides a PTFE-coated sodium ion battery active material and a preparation method thereof, which can effectively solve the problems of low electronic conductivity, high charge transfer resistance, poor capacity performance stability and cycle instability of existing sodium ion battery positive and negative electrode materials during the cycle process.

[0005] The technical solution of the present invention is achieved in this way:

[0006] On the one hand, an embodiment of the present application provides a PTFE-coated sodium ion battery active material, comprising polytetrafluoroethylene (PTFE) and an active substance, wherein the mass ratio of the polytetrafluoroethylene to the active substance is (0.02-0.09):1 or (0.2-0.3):1.

[0007] As a preferred embodiment, the active substance is hard carbon or sodium vanadium phosphate. When the active substance is hard carbon, the PTFE-coated sodium ion battery active material is a negative electrode active material for a sodium ion battery; when the active substance is sodium vanadium phosphate, the PTFE-coated sodium ion battery active material is a positive electrode active material for a sodium ion battery.

[0008] As a preferred embodiment, when the active material is hard carbon, the mass ratio of the polytetrafluoroethylene to the active material is (0.02-0.09):1;

[0009] When the active substance is sodium vanadium phosphate, the mass ratio of the polytetrafluoroethylene to the active substance is (0.2-0.3):1.

[0010] As a preferred embodiment, when the active material is hard carbon, the mass ratio of the polytetrafluoroethylene to the active material is 0.06:1;

[0011] When the active substance is sodium vanadium phosphate, the mass ratio of the polytetrafluoroethylene to the active substance is 0.24:1.

[0012] On the other hand, the present application also provides a method for preparing the PTFE-coated sodium ion battery active material, comprising the following steps:

[0013] S01, adding the active substance to the solvent (adding 50 ml of solvent for every 1 g to 2.5 g of the active substance), dispersing evenly, to obtain a first mixture;

[0014] S02, adding polytetrafluoroethylene to the first mixture of step S01, stirring evenly, to obtain a second mixture; the mass ratio of the polytetrafluoroethylene to the active substance is (0.02-0.09):1 or (0.2-0.3):1;

[0015] S03, drying the second mixture in step S02 to obtain a mixed precursor;

[0016] S04. In an inert gas, the mixed precursor of step S03 is subjected to a heat treatment to obtain a PTFE-coated sodium ion battery active material.

[0017] As a preferred embodiment, in step S01,

[0018] The solvent is at least one of deionized water and anhydrous ethanol, preferably a mixed solvent of anhydrous ethanol and deionized water.

[0019] The dispersion is achieved by an ultrasonic cell disruptor.

[0020] As a preferred embodiment, in step S02,

[0021] The stirring time is 4 h to 8 h, preferably 6 h.

[0022] When the active material is hard carbon, the stirring is performed by heating in a water bath.

[0023] The temperature of the water bath for hot stirring is 60°C to 100°C, preferably 80°C.

[0024] As a preferred implementation, in step S03,

[0025] The drying is oven drying (generally at 80° C. for 12 h) or freeze drying, preferably oven drying.

[0026] As a preferred implementation, in step S04,

[0027] The inert gas is argon or nitrogen.

[0028] When the active material is hard carbon, the heat treatment condition is heating at 300° C. to 500° C. for 4 h to 6 h.

[0029] Preferably, when the active material is hard carbon, the inert gas is nitrogen; and the heating treatment condition is heating at 400° C. for 5 hours.

[0030] When the active substance is sodium vanadium phosphate, the heat treatment condition is heating at 400° C. to 800° C. for 6 h to 10 h.

[0031] Preferably, when the active substance is sodium vanadium phosphate, the inert gas is nitrogen; and the heating treatment condition is heating at 600° C. for 8 hours.

[0032] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0033] The present application adopts PTFE to modify the active material of the sodium ion battery, and by controlling the dosage ratio of PTFE to the active material, the PTFE-coated sodium ion battery active material of the present application has a high ion transfer rate and a SEI interface layer with high mechanical strength. The preparation method of the present application is simple and fast, and the preparation cost is low, which is of great significance for the commercialization of sodium ion batteries. Through this application, the problems of low electronic conductivity, high charge transfer resistance, poor capacity performance stability and cycle instability of the existing positive and negative electrode materials of sodium ion batteries during the cycle process can be effectively solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a SEM image of the hard carbon used in one embodiment of the present application;

[0035] Figure 2 This is a SEM image of sodium vanadium phosphate used in one embodiment of the present application. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0038] The raw materials used in the following examples are all commercially available or homemade.

[0039] Example 1

[0040] This embodiment provides a PTFE-coated sodium ion battery negative electrode active material and a preparation method thereof, and the prepared PTFE-coated sodium ion battery negative electrode active material is applied to a sodium ion battery. The sodium ion battery includes a negative electrode, a separator, an electrolyte and a positive electrode. The negative electrode includes a negative electrode current collector and a PTFE-coated sodium ion battery negative electrode active material, and Whatman glass fiber is used as a separator. The positive electrode includes a positive electrode current collector and a positive electrode active material. The specific preparation method is as follows:

[0041] 1. Preparation process of a PTFE-coated sodium ion battery negative electrode active material:

[0042] 1.1. Add 2 g of hard carbon to 50 ml of a mixed solvent (mixed from 30 ml of deionized water and 20 ml of anhydrous ethanol), and use an ultrasonic cell crusher to ultrasonicate for 30 min to disperse it evenly to obtain a first mixture;

[0043] 1.2. Slowly add 4 g of polytetrafluoroethylene emulsion (3 wt%) to the first mixture through a peristaltic pump, and then transfer the mixture to a water bath at 80° C. and stir for 12 hours to obtain a second mixture;

[0044] 1.3. Heat the second mixture in a forced air oven at 80° C. for 12 hours to obtain a mixed precursor;

[0045] 1.4. In nitrogen, the mixed precursor is heated at 400° C. for 5 h to obtain a PTFE-coated sodium ion battery negative electrode active material (polytetrafluoroethylene-coated hard carbon negative electrode material).

[0046] The SEM image of the PTFE-coated sodium ion battery negative electrode active material prepared using hard carbon is shown in Figure 1 shown.

[0047] 2. Prepare the negative electrode: Use the PTFE-coated sodium ion battery negative electrode active material (HC@PTFE with a mass ratio of polytetrafluoroethylene and hard carbon of 0.1:1) as the negative electrode active material, conductive carbon black as the conductive agent, CMC as the binder, weigh 32 mg of PTFE@HC, 4 mg of conductive carbon black, 2 mg of CMC and 2 mg of SBR in a mass ratio of 8:1:1, grind the conductive agent, binder and negative electrode active material evenly according to a certain proportion, add a small amount of N-methylpyrrolidone and quickly grind into a slurry, scrape it onto the copper foil and then use a scraper to scrape it into a thin sheet with a thickness of 200 um, then put it in a vacuum oven and bake it at 80°C for 12 hours. Prepare the diaphragm: Cut the Whatman glass fiber diaphragm into a disc with a diameter of 16 mm with a cutting machine, and use it as a diaphragm after drying;

[0048] Prepare electrolyte: Use DME as solvent and prepare 1.0M NaPF6 in DME as electrolyte;

[0049] Preparation of positive electrode: Roll the sodium metal into a thin sheet and cut a disc with a diameter of 12 mm as the positive electrode;

[0050] 4. Assembly: Stack the prepared positive electrode, separator, and negative electrode tightly in sequence, drip the electrolyte to completely soak the separator, and then put the stacked parts into a button battery packaging machine for packaging to complete the sodium ion battery assembly.

[0051] Example 2

[0052] The embodiment of the present invention provides a PTFE-coated sodium ion battery positive electrode active material and a preparation method thereof, and the prepared PTFE-coated sodium ion battery negative electrode active material is applied to a sodium ion battery. The sodium ion battery includes a negative electrode, a separator, an electrolyte and a positive electrode. The negative electrode includes a negative electrode current collector and a negative electrode active material, and Whatman glass fiber is used as a separator. The positive electrode includes a positive electrode current collector and a PTFE-coated sodium ion battery positive electrode active material. The specific preparation method is as follows:

[0053] 1. Preparation process of a PTFE-coated sodium ion battery positive electrode active material:

[0054] 1.1. Add 2.5 g of sodium vanadium phosphate to 50 ml of a mixed solvent (mixed with 30 ml of deionized water and 20 ml of anhydrous ethanol), and use an ultrasonic cell crusher to disperse the mixture evenly for 30 min to obtain a first mixture;

[0055] 1.2. Slowly add 20 g of polytetrafluoroethylene emulsion (3 wt%) into the first mixture through a peristaltic pump and stir magnetically for 6 hours to obtain a second mixture;

[0056] 1.3. Heat the second mixture in a forced air oven at 80° C. for 12 hours to obtain a mixed precursor;

[0057] 1.4. In nitrogen, the mixed precursor is heated at 600° C. for 8 h to obtain a PTFE-coated sodium ion battery positive electrode active material (polytetrafluoroethylene-coated sodium vanadium phosphate positive electrode material).

[0058] The SEM image of the PTFE-coated sodium ion battery negative electrode active material prepared using sodium vanadium phosphate is shown in Figure 2 shown.

[0059] 2. Preparation of positive electrode: PTFE-coated sodium ion battery positive electrode active material (NVP@PTFE with a mass ratio of sodium vanadium phosphate and tetrafluoroethylene of 2.5:1) was used as the positive electrode active material, conductive carbon black was used as the conductive agent, and CMC was used as the binder. 32 mg of NVP@PTFE, 4 mg of conductive carbon black, 2 mg of CMC and 2 mg of SBR were weighed in a mass ratio of 8:1:1. The conductive agent, binder and positive electrode active material were evenly ground in a certain proportion, a small amount of N-methylpyrrolidone was added and quickly ground into a slurry, which was scraped onto a copper foil and then scraped into a thin sheet with a thickness of 200 um with a scraper, and then placed in a vacuum oven and baked at 80°C for 12 h.

[0060] Preparation of diaphragm: Cut Whatman glass fiber diaphragm into discs with a diameter of 16 mm using a cutting machine, and use them as diaphragms after drying;

[0061] Prepare electrolyte: Use DME as solvent and prepare 1.0M NaPF6 in DME as electrolyte;

[0062] Preparation of negative electrode: Roll the sodium metal into a thin sheet and cut a disc with a diameter of 12 mm as the negative electrode;

[0063] 4. Assembly: Stack the prepared positive electrode, separator, and negative electrode tightly in sequence, drip the electrolyte to completely soak the separator, and then put the stacked parts into a button battery packaging machine for packaging to complete the sodium ion battery assembly.

[0064] Comparative Example 1

[0065] This embodiment provides a first control battery, and its preparation method is similar to that of Example 1, except that this embodiment uses polytetrafluoroethylene and hard carbon in a mass ratio of 0.01:1 as the active material of the negative electrode of the sodium ion battery, and the rest is the same as Example 1.

[0066] Comparative Example 2

[0067] This embodiment provides a second control battery, and its preparation method is similar to that of Example 1, except that this embodiment uses polytetrafluoroethylene and hard carbon in a mass ratio of 0.1:1 as the active material of the negative electrode of the sodium ion battery, and the rest is the same as Example 1.

[0068] Comparative Example 3

[0069] The embodiment of the present invention provides a third control battery, and its preparation method is similar to that of Example 2, except that this embodiment uses polytetrafluoroethylene and sodium vanadium phosphate in a mass ratio of 0.1:1 as the active material of the positive electrode of the sodium ion battery, and the rest is the same as Example 2.

[0070] Comparative Example 4

[0071] The embodiment of the present invention provides a fourth control battery, and its preparation method is similar to that of Example 2, except that this embodiment uses polytetrafluoroethylene and sodium vanadium phosphate in a mass ratio of 0.4:1 as the active material of the positive electrode of the sodium ion battery, and the rest is the same as Example 2.

[0072] Effect Example

[0073] Electrochemical performance tests were performed on the sodium ion batteries of Example 1 and Comparative Examples 1-2, and Example 2 and Comparative Examples 3-4, respectively:

[0074] The cycle performance was tested by a conventional battery testing method, and the charge and discharge specific capacity at different current densities and the capacity retention rate after different cycles were tested. The results are shown in Tables 1 and 2. Table 1 shows the electrochemical properties of the batteries prepared in Example 1 and Comparative Examples 1 to 2 provided in the embodiments of the present invention; Table 2 shows the electrochemical properties of the batteries prepared in Example 2 and Comparative Examples 3 to 4 provided in the embodiments of the present invention; It can be seen from Tables 1 and 2 that the sodium ion battery active material provided by the present invention has a high charge and discharge specific capacity and capacity retention rate after the same number of cycles at different current densities.

[0075] Table 1 Test results of electrochemical performance of batteries prepared in Example 1 and Comparative Examples 1-2

[0076]

[0077]

[0078] Table 2 Test results of electrochemical performance of batteries prepared in Example 2 and Comparative Examples 3-4

[0079]

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A PTFE-coated sodium ion battery active material, characterized in that: The invention comprises polytetrafluoroethylene and an active substance, wherein the mass ratio of the polytetrafluoroethylene to the active substance is (0.02-0.09):1 or (0.2-0.3):

1.

2. The PTFE-coated sodium ion battery active material according to claim 1, characterized in that: The active substance is hard carbon or sodium vanadium phosphate.

3. The PTFE-coated sodium ion battery active material according to claim 2, characterized in that: When the active material is hard carbon, the mass ratio of the polytetrafluoroethylene to the active material is (0.02-0.09):1; When the active substance is sodium vanadium phosphate, the mass ratio of the polytetrafluoroethylene to the active substance is (0.2-0.3):

1.

4. The PTFE-coated sodium ion battery active material according to claim 2, characterized in that: When the active material is hard carbon, the mass ratio of the polytetrafluoroethylene to the active material is 0.06:1; When the active substance is sodium vanadium phosphate, the mass ratio of the polytetrafluoroethylene to the active substance is 0.24:

1.

5. The method for preparing the PTFE-coated sodium ion battery active material according to any one of claims 1 to 4, characterized in that: The steps include: S01, adding the active substance to the solvent and dispersing it evenly to obtain a first mixture; S02, adding polytetrafluoroethylene to the first mixture of step S01, stirring evenly, to obtain a second mixture; the mass ratio of the polytetrafluoroethylene to the active substance is (0.02-0.09):1 or (0.2-0.3):1; S03, drying the second mixture in step S02 to obtain a mixed precursor; S04. In an inert gas, the mixed precursor of step S03 is subjected to a heat treatment to obtain a PTFE-coated sodium ion battery active material.

6. The method for preparing the PTFE-coated sodium ion battery active material according to claim 5, characterized in that: In step S01, The solvent is at least one of deionized water and anhydrous ethanol; The dispersion is achieved by an ultrasonic cell disruptor.

7. The method for preparing the PTFE-coated sodium ion battery active material according to claim 5, characterized in that: In step S02, the stirring time is 4 hours to 8 hours.

8. The method for preparing the PTFE-coated sodium ion battery active material according to claim 5, characterized in that: In step S02, when the active material is hard carbon, the stirring is water bath heating stirring; The temperature of the water bath for hot stirring is 60°C to 100°C.

9. The method for preparing the PTFE-coated sodium ion battery active material according to claim 5, characterized in that: In step S04, the inert gas is argon or nitrogen.

10. The method for preparing the PTFE-coated sodium ion battery active material according to claim 5, characterized in that: In step S04, When the active material is hard carbon, the heat treatment condition is heating at 300° C. to 500° C. for 4 h to 6 h; When the active substance is sodium vanadium phosphate, the heat treatment condition is heating at 400° C. to 800° C. for 6 h to 10 h.